USING BOARD RACE GAME TO IMPROVE STUDENTS’ VOCABULARY MASTERY (A study conducted at SMP Anugrah Tondano) - Sri Yupingkayani Pomontolo; Paula Hampp; Paula Rombepajung (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
"Using Board Race Game to promote the students' vocabulary mastery at VIII grade kids of SMP Anugrah Tondano" was the topic of this study. This study sought to determine if the Board Race game improved pupils' vocabularies. This study was carried out using a quantitative approach. This study used an experimental pre-test and post-test design in one class. This study focused on the first grade at SMP Anugrah Tondano, which included 20 pupils. Each test consisted of 20 numbers, which were delivered to the pupils. According to the study's findings, the post-test's mean score (68) was higher than the pre-test's (38.25). Based on the findings, it was possible to draw the conclusion that utilizing a board race game to teach kids vocabulary was beneficial since it might motivate them to study and help them retain more words.